Associations between public health measures and mortality among hospitalised COVID-19 patients: a cross-sectional study in Malaysia - Siti Najiha Md Asari; Nazarudin Bin Safian; Noor Khalili Mohd Ali; Nadiatul Ima Zulkifli (Scientific Reports)
Abstract Identifying risk and protective factors associated with COVID-19 mortality among hospitalised patients is essential for improving clinical outcomes and guiding public health interventions. This study examined demographic, clinical, and public health factors associated with in-hospital mortality among COVID-19 patients in Malaysia. We conducted a cross-sectional analysis of epidemiological and clinical data from 1,795 confirmed COVID-19 patients admitted to a designated hospital in Negeri Sembilan between January and December 2021. Variables included age, sex, comorbidities, clinical symptoms, vaccination status, screening method (e.g., close contact, symptomatic, pre-procedure), and RT-PCR cycle threshold (CT) values. Univariable and multivariable logistic regression analyses were used to identify factors associated with mortality. A total of 224 patients (12.5%) died during hospitalisation. Mortality was significantly associated with age ≥ 71 years (aOR 14.02, 95% CI: 5.98–32.83), male sex (aOR 1.52, 95% CI: 1.11–2.07), and comorbidities including stroke (aOR 4.3, 95% CI: 1.3–14.06), chronic kidney disease (aOR 4.23, 95% CI: 1.99–9), and cancer (aOR 3.3, 95% CI: 1.1–10). Protective factors included complete COVID-19 vaccination (aOR 0.31, 95% CI: 0.11–0.98), close contact screening (aOR 0.45, 95% CI: 0.3–0.67), and symptomatic screening (aOR 0.59, 95% CI: 0.37–0.94). Complete vaccination and early case detection through close contact and symptomatic screening were associated with reduced mortality among hospitalised COVID-19 patients. These findings highlight the importance of strengthening vaccination programmes and early detection strategies to inform future pandemic preparedness and optimise hospital resource allocation.